The Relation between Skills and Job Security: Identifying the Contractual Return to Skills - Ron Diris; Olaf Van Vliet (Institute of Labor Economics (IZA), 2022)
The last decades have shown that the traditional steady job with a permanent contract is on the decline. While permanent contracts and the insider position that they bring are highly valued by workers, research on the returns to human capital have predominantly focused on wages as subject of that return. This study uses PIAAC data from 29 countries to estimate how skills relate to the odds of obtaining a permanent contract, versus alternative contractual arrangements for employees. Our pooled analysis shows that skills substantially relate to having a permanent contract across the full sample. Numeracy skills contribute more than literacy skills; a difference that is largely driven by sorting to occupations and industries. We further identify substantial heterogeneities across countries, in which either no skills, only numeracy skills or only literacy skills significantly predict permanent employment at the country level, but never both. Moreover, this "contractual return to skills" differs substantially from the traditional wage return to skills across countries. We find suggestive evidence that these differences relate to demand factors and labour market institutions.
Keywords: I21; J24; 330; skills; human capital; labour markets; temporary employment